2022
DOI: 10.3389/fcvm.2021.777206
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mechanics Differ in Subtypes of Aortic Stenosis Following Transcatheter Aortic Valve Replacement

Abstract: BackgroundLeft ventricular (LV) mechanics are impaired in patients with severe aortic stenosis (AS). We hypothesized that there would be differences in myocardial mechanics, measured by global longitudinal strain (GLS) recovery in patients with four subtypes of severe AS after transcatheter aortic valve replacement (TAVR), stratified based upon flow and gradient.MethodsWe retrospectively evaluated 204 patients with severe AS who underwent TAVR and were followed post-TAVR at our institution for clinical outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Also, other studies have shown that an improvement was found in LV-GLS at one-year post-TAVR, but no significant changes were recorded in LVEF, suggesting that strain may be a more sensitive parameter for changes in LV mechanics after TAVR. 7 On the other hand, as shown in other studies, NT-proBNP values may be influenced by several comorbidities, such as obesity, renal dysfunction, etc., thus altering its prognostic and risk stratification value. 8 Right ventricular dysfunction is a well-known independent adverse prognostic factor in patients with severe aortic stenosis requiring surgical replacement.…”
Section: Discussionmentioning
confidence: 87%
“…Also, other studies have shown that an improvement was found in LV-GLS at one-year post-TAVR, but no significant changes were recorded in LVEF, suggesting that strain may be a more sensitive parameter for changes in LV mechanics after TAVR. 7 On the other hand, as shown in other studies, NT-proBNP values may be influenced by several comorbidities, such as obesity, renal dysfunction, etc., thus altering its prognostic and risk stratification value. 8 Right ventricular dysfunction is a well-known independent adverse prognostic factor in patients with severe aortic stenosis requiring surgical replacement.…”
Section: Discussionmentioning
confidence: 87%
“…But the current results were controversial. Some studies revealed a significant prognostic value of LVLS ( 17 , 28 ) and concluded baseline LVLS was associated with poor survival ( 11 , 23 ), but others also found it not associated with a survival benefit ( 15 , 16 , 18 , 22 ). This meta-analysis found that the impaired pooled LVLS was associated with an increased risk for combined ACM and MACE.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In low-flow low-gradient (LFLG) AS patients, GLS improved but did not normalize, suggesting a degree of irreversible adverse remodeling and myocardial damage. 26 , 28 In LFLG AS, GLS was a stronger predictor of LV recovery after TAVR than LVEF. 22 …”
Section: Systolic Function Assessment and Predictors Of Recovery Afte...mentioning
confidence: 91%
“…27 In low-flow low-gradient (LFLG) AS patients, GLS improved but did not normalize, suggesting a degree of irreversible adverse remodeling and myocardial damage. 26,28 In LFLG AS, GLS was a stronger predictor of LV recovery after TAVR than LVEF. 22 Additionally, the role of LV mass index (LVMi) regression in LVEF recovery has been highlighted among patients in the PARTNER I, II, and S3 trials and registries.…”
Section: Echocardiographymentioning
confidence: 94%